2016
DOI: 10.1136/bjophthalmol-2015-307678
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between high serum ferritin level and glaucoma in a South Korean population: the Kangbuk Samsung health study

Abstract: High serum ferritin level was associated with a high risk of glaucoma in men, but not in women. Because serum ferritin is related to oxidative stress and inflammation, it might play a role in glaucoma development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
0
28
2
1
Order By: Relevance
“…The retrospective cross‐sectional Kangbuk Samsung health study ( N = 164 029) found similar results in men (highest quartile OR [95% CI]: 1.18 [1.03–1.34]; Gye et al. ). In contrast, in female patients with iron deficiency anaemia, a thinner peripapillary retinal nerve fibre layer was reported compared to controls; however, it is not known whether it is the iron deficiency or the anaemia that caused this finding (Cikmazkara & Ugurlu ).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The retrospective cross‐sectional Kangbuk Samsung health study ( N = 164 029) found similar results in men (highest quartile OR [95% CI]: 1.18 [1.03–1.34]; Gye et al. ). In contrast, in female patients with iron deficiency anaemia, a thinner peripapillary retinal nerve fibre layer was reported compared to controls; however, it is not known whether it is the iron deficiency or the anaemia that caused this finding (Cikmazkara & Ugurlu ).…”
Section: Resultsmentioning
confidence: 77%
“…Regarding total and dietary iron consumption, the same research group reported in another study (N = 6316) an increasing OR per quintile of total consumption of iron, but a decreasing OR per quintile of dietary iron ). In another cross-sectional population-based study (N = 17 476), it was shown that a high serum ferritin level was associated with a higher risk of glaucoma (highest quartile OR [95% CI]: 1.89 [1.32-2.72]; Lin et al 2014 Gye et al 2016). In contrast, in female patients with iron deficiency anaemia, a thinner peripapillary retinal nerve fibre layer was reported compared to controls; however, it is not known whether it is the iron deficiency or the anaemia that caused this finding (Cikmazkara & Ugurlu 2016).…”
Section: Minerals and Trace Elementsmentioning
confidence: 99%
“…Our cohort consisted of mostly middle aged Asians with higher socioeconomic and education levels and urban habitation with the highest annual PM concentrations in the world. Thus, these characteristics can contribute to more increase in the amount of mobilized iron especially in men than women in our cohort [8,[21][22][23][24][25][26]. The large difference in serum ferritin level between men and women can contribute to much higher lifetime iron stores in men than in women.…”
Section: Study Design and Populationmentioning
confidence: 83%
“…all the previous studies enrolled females, who represented more than half of the total number of subjects, in contrast to this study. Although serum ferritin decreases with age in males and increases with age in females, the factor with the greatest effect on the discrepant level of ferritin is sex [24,36]. Hormonal effects and increased iron loss can cause physiological differences in iron homeostasis and biomarker distributions between males and females.…”
Section: Plos Onementioning
confidence: 99%
“…In the low BMI group of females, those with POAG had lower intakes of most of nutrients than those without POAG, but this was not true for males. Some studies have reported differences in the prevalence and risk factors for OAG between males and females [3,10,48,49]. Estrogen-related factors such as the effect on IOP and their neuroprotective effects have been proposedas possible mechanisms to explain the observed sex differences in POAG prevalence [50,51].…”
Section: Discussionmentioning
confidence: 99%